Word order variation of the verbal sentences in Amqi Akkadian - Westhuizen, J. P. van der (Journal for semitics, 1994)
The ongoing internal and external turmoil in Syria-Palestine during the late bronze age was the reason for the correspondence between the vassals of this area and their sovereign, the pharaoh of Egypt. These letters were written by scribes, in the WPA (Western Peripheral Akkadian) dialect, a Peripheral Akkadian (PA) dialect with some West Semitic (WS) trends. One such trend is the word order, and the variation thereof, in verbal sentences. This variation in word order was to effect some special emphasis of the appropriate element in the specific sentence. The variation in word order was brought about by certain (emphasizing) words and constructions such as anuma, anita, inuma, and amurmi subject fronting and object fronting; parallel sentence arrangement and chiastic sentence arrangement.